Higiene oral y pérdida de primeras molares permanentes en niños de 6 a 12 años en la I.E. Sachachorro Iquitos-2025 - Manzur Ancco, Dariana Josetty (2025)
OBJECTIVE: To examine the relationship between oral hygiene and the loss of first permanent molars in children aged 6 to 12 at I.E. Sachachorro, Iquitos, 2025. METHODS: A quantitative, non-experimental, cross-sectional, and correlational study was conducted with 106 schoolchildren. Oral hygiene was assessed using the Simplified Oral Hygiene Index (IHOS), validated by Greene and Vermillion, while first permanent molar loss was recorded through direct clinical observation using a specially designed data collection form. RESULTS: The prevalence of first permanent molar loss was low (2.8%), with an average age of 9.36 years. Most children exhibited regular oral hygiene (57%), followed by good hygiene (41.5%) and excellent hygiene (0.9%). No significant associations were found between oral hygiene and tooth loss (p=0.114), sex (p=0.539), or age (p=0.097). Children aged 6–7 showed better oral hygiene, while those 8–12 years were mainly in the regular category. Slight male predominance was observed (53.8%). CONCLUSIONS: Oral hygiene was not significantly associated with first permanent molar loss in this population. However, the findings emphasize the need to strengthen educational strategies to promote proper oral hygiene habits among schoolchildren.